Environmental Education - a school practice using the theme of soils (Research, Society and Development, 2020)
This work aims to contribute to the formation of critical thinking related to the environment, preservation and sustainability through Environmental Education, using the theme of soils in the school environment. In addition to this, working with the interrelationship between human beings and the environment, developing a cooperative spirit and committed to the future of the planet. The methodology was used in the form of workshops with thematic soils and vermicomposting, the workshops were developed with students from the 1st and 5th year of Elementary School I at a Municipal School in Santa Maria, RS. The construction of knowledge was sought through practical activities that involved the participation and contribution of all involved. In this way, we sought to collaborate with Environmental Education, sensitizing students to the importance of soil and the reuse of solid residues, especially organic ones via vermicomposting, projecting that this practice extends beyond the school environment.